Selecting anti-speeding messages for roadside application. (October 2018) - Glendon, A. Ian; Lewis, Ioni; Levin, Kfir; Ho, Bonnie
Highlights: Of 18 messages, 3 were rated more effective for other drivers than for self-as-driver. Of 18 messages, 2 were rated more effective for self-as-driver than for divers in general. There was considerable variation between respondents' views on message effectiveness. But some messages were ranked consistently higher than others for effectiveness. Abstract: Purpose: Analyze qualitative and quantitative data to determine the relative effectiveness of theoretically-developed anti-speeding messages, as judged by relatively inexperienced and experienced drivers, both for themselves as a driver, and for drivers in general. Method: Eight focus groups and three individual interviews were conducted. Participants initially completed a questionnaire, ranking sets of three anti-speeding messages representing each of the six components of protection motivation theory (PMT). Participants were encouraged to write down the reasons for their rankings. During group and individual facilitation sessions, the rankings and reasons for them were discussed to identify salient reasons for participants' judgments. The ranking data were analyzed quantitatively, with individual and group-based comments being analyzed thematically. Results: Quantitative analyses of message pairs revealed five third-person effects (TPEs). Three messages were perceived as more relevant to drivers in general than to the participant-as-driver while two were associated with reverse TPEs, which participants perceived as more relevant to themselves-as-driver than for drivers in general. For four PMT components (rewards, self-efficacy, response efficacy, response costs), one or more messages received significantly higher rankings than one or more other messages representing the same component. Substantial variation was found within the individual and group discussion comments in respect of nearly all the messages, reflecting different driver perspectives and demographics. Discussion: A general preference for shorter messages was evident, leading to a revision of most of the messages comprising the stimuli for this study. On the basis of the focus group and interview responses, consideration was given as to which messages would be recommended for a pilot field study.